2022
DOI: 10.1136/heartjnl-2022-321698
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of left ventricular global longitudinal strain in atrial mitral regurgitation

Abstract: ObjectiveLeft atrial (LA) and left ventricular (LV) mechanics are impaired in patients with atrial functional mitral regurgitation (AFMR), but their prognostic value in this subset of patients remains unknown. The present study aimed to evaluate the association between LA and LV longitudinal strain and clinical outcomes in patients with AFMR.MethodsA total of 197 patients (mean age 73±10 years, 44% men) with at least moderate AFMR were retrospectively identified. LV global longitudinal strain (GLS) and left at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In this framework of atrial FMR, a previous study by Tang et al 7 showed that among patients with atrial fibrillation and absent atrial contraction, a prevailing effect of subtle abnormal LV mechanics and reduced annular dynamics during systole rather than isolated LA strain were the determinants of severe atrial FMR. This raised the hypothesis that atrial FMR may not be purely an atrial disorder, and the study published by Meucci et al in this journal supports this theory by showing that among patients with moderate and severe atrial FMR the impairment of LV global longitudinal strain (GLS) rather than LA reservoir strain had a pathogenetic and a prognostic role 8. Notably, the authors measured LV function with GLS, a marker of subtle LV dysfunction; this parameter is less dependent on preload than EF, which may be overestimated in the setting of volume overload by significant FMR.…”
mentioning
confidence: 79%
“…In this framework of atrial FMR, a previous study by Tang et al 7 showed that among patients with atrial fibrillation and absent atrial contraction, a prevailing effect of subtle abnormal LV mechanics and reduced annular dynamics during systole rather than isolated LA strain were the determinants of severe atrial FMR. This raised the hypothesis that atrial FMR may not be purely an atrial disorder, and the study published by Meucci et al in this journal supports this theory by showing that among patients with moderate and severe atrial FMR the impairment of LV global longitudinal strain (GLS) rather than LA reservoir strain had a pathogenetic and a prognostic role 8. Notably, the authors measured LV function with GLS, a marker of subtle LV dysfunction; this parameter is less dependent on preload than EF, which may be overestimated in the setting of volume overload by significant FMR.…”
mentioning
confidence: 79%
“…Bursi and Lee propose in an editorial4 that perhaps ‘atrial’ secondary MR actually is a disease of the ventricle with mitral annular dilation and dysfunction reflecting increased LV myocardial wall stress or elevated LV filling pressures. The data from Meucci and colleagues3 supports this concept given that LV strain, not LA strain, was predictive of clinical outcomes in patients with ‘atrial’ secondary MR. They suggest that ‘This novel paradigm carries important therapeutic implications.…”
mentioning
confidence: 86%
“…Unlike primary MR due to leaflet disease or secondary MR due to LV dilation and systolic dysfunction, there are few clinical studies addressing prediction of clinical outcomes in this patient group. In this issue of Heart , Meucci and colleagues3 measured LV global longitudinal strain (GLS) and LA reservoir strain (LAS) in 197 patients (mean age 73 years, 56% women, 92% in atrial fibrillation) with at least moderate atrial functional MR. On multivariable Cox regression analysis, LAS was not associated with adverse clinical outcomes but LV GLS was an independent predictor or all-cause mortality over a median follow-up of 5.8 years (figure 3).…”
mentioning
confidence: 99%
“…As in nearly all the studies with a cross-sectional design [27,28], the impact of the longitudinal changes in echocardiographic measures, including LVEF and LVOT-VTI, remains to be evaluated, particularly in patients undergoing mitral valve intervention. Because of the retrospective nature of the work, other metrics of LV systolic function (e.g., GLS and 3D-LVEF) were not available in most of the patients.…”
Section: Study Limitationsmentioning
confidence: 99%